2018
DOI: 10.3389/fnagi.2018.00129
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Disruption Induced Cognitive Impairment Is Associated With Increase of Inflammatory Cytokine

Abstract: Patients with diabetes suffer the higher risk of dementia and the underlying pathological mechanism of cognitive dysfunction in diabetes is not fully understood. In this study, we explore whether the cognitive impairment in the diabetic rat is associated with increased blood brain barrier (BBB) permeability and the change of the inflammatory cytokine. Experimental diabetic rats were induced by single intraperitoneal injection of streptozotocin (STZ). Cognitive function was evaluated by Morris water maze in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…In particular, the tight junctions between the brain vascular endothelial cells (BVECs), comprising occludin proteins, claudin proteins, and junctional adhesion molecules, are vital for the structural and functional integrity of BBB . Therefore, BBB breakdown, due to disruption of the tight junctions, inflammatory responses, or other risk factors, may enhance its permeability and induce the leakage of harmful substances from blood vessels into the brain, contributing to the process of AD . Very recently, Nation et al demonstrated that individuals with early cognitive dysfunction develop brain capillary damage and BBB breakdown in the hippocampus and established BBB breakdown as an early biomarker of human cognitive dysfunction in individuals with and without Aβ or phosphorylated tau (pTau) positivity.…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the tight junctions between the brain vascular endothelial cells (BVECs), comprising occludin proteins, claudin proteins, and junctional adhesion molecules, are vital for the structural and functional integrity of BBB . Therefore, BBB breakdown, due to disruption of the tight junctions, inflammatory responses, or other risk factors, may enhance its permeability and induce the leakage of harmful substances from blood vessels into the brain, contributing to the process of AD . Very recently, Nation et al demonstrated that individuals with early cognitive dysfunction develop brain capillary damage and BBB breakdown in the hippocampus and established BBB breakdown as an early biomarker of human cognitive dysfunction in individuals with and without Aβ or phosphorylated tau (pTau) positivity.…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 99%
“…176 Therefore, BBB breakdown, due to disruption of the tight junctions, inflammatory responses, or other risk factors, may enhance its permeability and induce the leakage of harmful substances from blood vessels into the brain, contributing to the process of AD. 175,177 Very recently, Nation et al 178 demonstrated that individuals with early cognitive dysfunction develop brain capillary damage and BBB breakdown in the hippocampus and established BBB breakdown as an early biomarker of human cognitive dysfunction in individuals with and without Aβ or phosphorylated tau (pTau) positivity. Therefore, the authors concluded that neurovascular dysfunction might be a previously underappreciated promotor of AD, independent of the classic pathophysiological hallmarks.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Studies with other patient populations and disease models have also suggested a link between autoimmune-mediated BBBd and cognitive/neuropsychiatric deficits (and thus a CNS involvement) [7][8][9]. Findings from the field of rheumatoid arthritis (RA) show that CNS involvement in RA occurs possibly due to BBBd associated with chronic inflammation and that circulating immune complexes may cause neuroinflammatory responses in the brain [36].…”
Section: Sdmt Pasat Tmt a Tmt B/a Vlmt Totalmentioning
confidence: 99%
“…Additionally, we compared the patients' performance in each neuropsychological test with a group of healthy controls (HC) after adjusting for confounding variables. Last but not least, since experimental and observational studies have suggested a link between autoimmune-mediated BBBd and cognitive deficits [7][8][9], we investigated the association between the integrity of the BBB (as measured by the cerebrospinal fluid (CSF)/serum albumin quotient determined during the time of first CAPD diagnosis) and current cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…18 Glucose levels were assessed for 3 weeks after STZ injection to ensure that diabetes was not reversed. In week 14, the diabetic rats were administered the WE and EE of TWK10-fermented soy milk for 6 weeks (weeks [14][15][16][17][18][19][20], and after performing the Morris water maze (MWM) test, the rats were fasted overnight and sacrificed. Blood and aortic and brain tissues were harvested.…”
Section: Experimental Groupsmentioning
confidence: 99%